Unjuk Kerja Mesin Perajang Biomassa Tipe Slicer Untuk Merajang Batang Singkong - Saputra, Rio Dwi; Asmara, Sandi; Tusi, Ahmad; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2025)
This study aims to evaluate the performance of the Rabakong slicer-type machine and compare it with previous models. A Completely Randomized Design (CRD) was used with two factors: machine rotation speed (1500, 2000, and 2700 RPM) and the number of cassava stems input (2, 3, and 4 stems). Each treatment was repeated three times for 10 minutes. Observed parameters included work capacity (kg/h), fuel consumption (l/h), percentage of product loss, slicing uniformity (%), and ergonomic aspects of operator performance. The results showed the highest work capacity of 522.2 kg/h at 2700 RPM with 4 stems. The lowest product loss (0.82%) occurred at 2000 RPM with 3 stems, while the lowest fuel consumption (0,680 l/h) was recorded at 1500 RPM with 4 stems. The highest slicing uniformity (58%) was obtained at 2700 RPM, particularly for output passing through a 0.1 mm mesh. The Rabakong slicer-type machine falls under the moderate workload category with a CVL of 41–47% and an operator heart rate of 125–135 bpm, still within safe limits (Tarwaka, 2004). This machine outperforms its predecessor in capacity, uniformity, fuel efficiency, and operator comfort. Therefore, it is recommended as an effective solution for processing cassava stem waste into value-added products such as animal feed or compost.